Lao PDR - Labor Standards and Productivity in the Garments Export Sector : A Survey of Managers and Workers - World Bank (Washington, DC, 2012)
This report describes labor practices in the Lao garments export sector as seen by both management and labor. The main objective of this report is to present the differing perspectives on working conditions between managers and workers, and to explore ways in which the Lao garment sector could break out of this unsustainable situation. More specifically, insights on management practices, working conditions and worker motivation, as well as industry technology and workflow practices, are drawn from the survey and recommendations made on what firms, industry, government and development partners can do to boost productivity in the sector. This study seeks to investigate further possible factors contributing to low-productivity including management practices, working conditions and worker motivation, as well as industry technology and workflow practices. In order for the garment sector to progress, this study points to possibilities to increase worker wellbeing, reduce turnover and improve productivity through mutually reinforcing actions. Possible interventions include: a transition support program and improved labor market information systems to support labor force entry; better worker representation and dispute resolution mechanisms; and, a factories improvement program that would include monitoring/certification systems to provide incentives for firms to improve conditions as a means of accessing elusive premium buyers.